Writing a review article for Psychological Bulletin. [article]. - Bern, Daryl J.
Guidelines and tips are offered for writing a Psychological Bulletin review article that will be accessible to the widest possible audience. Techniques are discussed for organizing a review into a coherent narrative, and the importance of giving readers a clear take-home message is emphasized. In addition, the advice is given for rewriting a manuscript that has been reviewed and returned with an invitation to revise and resubmit. --(from the author).